Influence of Surveillance Methods in the Detection of Sports Injuries and Illnesses - Sonoko Mashimo; Takaaki Hogan; Satoru Nishida; Yumi Watanabe; Yuya Matsuki; Hirokazu Suhara; Naruto Yoshida (International Journal of Sports Physical Therapy)
# Background